A kind of rubber resin and its preparation process

By introducing single micelle core-shell SiO2 nanoparticles and polyamide into the boron phenolic resin to form a composite resin, the problem of reducing thermal stability of boron phenolic resin at high temperature is solved, and the high thermal stability and impact strength of the resin are achieved.

CN118638283BActive Publication Date: 2025-04-08PUYANG BINDER CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410879352.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2025-04-08
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

The thermal stability of existing boron phenolic resins decreases at high temperatures, affecting their application.

Method used

The preparation process of single micelle core-shell SiO2 nanoparticles and polyamide composite modified phenolic resin is adopted, and the thermal stability and toughness of the resin are enhanced through the introduction of boron elements, the hydroxymethylation reaction of polyamide and the interface enhancement of single micelle core-shell SiO2 nanoparticles.

Benefits of technology

The excellent thermal stability and high impact strength of the rubber resin at high temperatures are achieved, and the overall performance of the resin is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118638283B_ABST
    Figure CN118638283B_ABST
Patent Text Reader

Abstract

The present invention provides a rubber resin and a preparation process thereof, belonging to the technical field of modified phenolic resins. 2 The nanoparticles and polyamide are composited to modify the phenolic resin to obtain the rubber resin; the specific process steps are: S1, by weight, 3.8-4.6 parts of phenol and 1 part of boric acid are added to a three-necked flask, the pH is adjusted to acidic, 0.05-0.1 parts of water-carrying agent are added, the temperature is raised to 100°C, the temperature is gradually raised to 180°C for a total reaction of 5h, and a reaction solution is obtained; S2, the reaction solution obtained in S1 is cooled to 90°C, 0.5-0.8 parts of polyamide, 1-2 parts of paraformaldehyde and single micelle core-shell SiO 2 0.2-0.4 parts of nanoparticles, stirring and heating to 105-115°C, continuing the reaction for 0.5-2h, vacuum drying at 115-120°C for 2-8h, and quickly discharging to obtain a gel; S3, adding 0.5-1 parts of a 10% by mass hexamethylenetetramine aqueous solution to the gel obtained in S2, stirring for 5-30min, and then standing for 30-50min, crushing into powder, and obtaining the rubber resin. The resin obtained by the present invention has excellent thermal stability and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of modified phenolic resins, and in particular relates to a rubber resin and a preparation process thereof. Background Art

[0002] Petroleum resin is a byproduct of petroleum cracking, mainly used in the manufacture of adhesives, coatings, rubbers and plastics. C5 is a C5 olefin produced in the process of petroleum cracking. C5 is also called C5 resin and aliphatic hydrocarbon resin. It is divided into three types: general type, blending type and colorless transparent type, with an average molecular weight of 1000 to 2500. Phenolic resin is a type of thermosetting resin made by the condensation reaction of phenols and aldehydes. It is widely used in the manufacture of insulating materials, adhesives, coatings, etc. These three substances are closely related in the chemical industry.

[0003] Boron phenolic resin is a type of resin that introduces boron into the phenolic resin structure. The introduction of boron greatly increases the thermal stability of phenolic resin, but at the same time, boron can produce a three-dimensional network cross-linked structure containing boron through self-crosslinking, which increases the crosslinking degree and brittleness of boron phenolic resin, which is not conducive to the application of boron phenolic resin. At present, the main methods for toughening and modifying boron phenolic resin include rubber modification, silicone modification, and oil compound modification. Through modification methods, the impact toughness / impact strength of the resin is greatly improved.

[0004] The existing Chinese invention patent with publication number CN117264150A discloses a thermosetting phenolic resin and a preparation method thereof. Both the modifier and the strengthener molecules contain phenol groups and can participate in the reaction of the phenolic resin. The modifier is a cage-type polysiloxane structure and forms a core-shell structure with the main molecular chain of the phenolic resin. The modifier molecule contains a boric acid group and forms a borate covalent bond during the curing process of the phenolic resin, thereby increasing the toughness and strength of the phenolic resin. The strengthener molecular chain contains a polyester segment, which is made of a long carbon chain raw material and can increase the flexibility of the polyester segment. In the preparation process of the phenolic resin, a cross-structure of the polysiloxane segment and the main chain segment of the phenolic resin molecule can be formed, thereby further improving the toughness of the phenolic resin.

[0005] However, since the introduced siloxane segments are prone to thermal decomposition and thermal oxidation at high temperatures, the thermal stability of the resin is greatly reduced at high temperatures. Summary of the invention

[0006] In order to solve the problems existing in the background technology, the present invention provides a rubber resin and a preparation process thereof, and the obtained resin has excellent thermal stability and toughness (impact strength).

[0007] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a process for preparing a rubber resin, wherein single micellar core-shell SiO2 nanoparticles and polyamide are composite-modified with a phenolic resin to obtain the rubber resin;

[0008] The specific process steps are as follows:

[0009] S1. Add 3.8-4.6 parts of phenol and 1 part of boric acid into a three-necked flask (the molar ratio of the two is about 2.5-3:1) by weight, adjust the pH to acidic, add 0.05-0.1 parts of water-carrying agent to remove the water produced by the esterification reaction, heat to 100°C, and then gradually heat to 180°C for a total reaction of 5h to obtain a reaction solution;

[0010] S2, cooling the reaction solution obtained in S1 to 90°C, adding 0.5-0.8 parts of polyamide, 1-2 parts of paraformaldehyde and 0.2-0.4 parts of single micellar core-shell SiO2 nanoparticles, stirring and heating to 105-115°C, continuing the reaction for 0.5-2h until gelation occurs, vacuum drying at 115-120°C for 2-8h until almost no bubbles are generated, and quickly discharging the material to obtain a gel material;

[0011] S3, adding 0.5-1 parts of 10% by mass hexamethylenetetramine aqueous solution to the gel material obtained in S2, stirring for 5-30 minutes, and standing for 30-50 minutes to form a solid resin, and then crushing the solid resin into powder to obtain the rubber resin.

[0012] Furthermore, the preparation method of the single micellar core-shell SiO2 nanoparticles is as follows:

[0013] A1. Dissolve 6 g of polyether in 94 g of 0.85 M hydrochloric acid aqueous solution and stir at room temperature. The solution becomes clear and transparent, indicating that the polyether has formed micelles and obtained a homogeneous liquid.

[0014] A2, add 10mL of tetraethyl orthosilicate to the homogeneous liquid obtained in A1, stir at room temperature, the solution changes from oily turbidity to transparent, indicating that the silicon source precursor tetraethyl orthosilicate is hydrolyzed and condensed in the acidic aqueous solution to form a loose three-dimensional network shell structure, and has been successfully deposited on the interface between the hydrophobic segment and the hydrophilic segment of the micelle, to obtain a deposition liquid;

[0015] A3, after adding 0.8g of stop solution to the sediment solution obtained in A2, dialyze (molecular weight cutoff 8000-14400) for 48 hours, and replace the deionized water every about 1 hour to remove the HCl in the solution and small molecular impurities such as EtOH produced by hydrolysis; monitor the dialysis process by measuring the pH value of the dialysate; the initial pH value is lower than 1, and after 48 hours, the pH value reaches about 6, and the dialysis is terminated to obtain the dialysate;

[0016] A4. Filter the dialysate obtained in A3 with a 0.22 μm polytetrafluoroethylene filter to remove possible large particles, thereby obtaining the monomicelle core-shell SiO2 nanoparticles.

[0017] Furthermore, in A1, the stirring condition is: stirring at 500 r / min for 0.8-1.2 h.

[0018] Furthermore, in A2, the stirring condition is: stirring at 500 r / min for 1-2 h.

[0019] Furthermore, in A3, the stop solution used is dimethyldiethoxysilane.

[0020] Furthermore, in S1, the specific operation of adjusting the pH to acidic is: using a 35% by mass sulfuric acid aqueous solution to adjust the pH to 4-6.

[0021] Furthermore, the water-carrying agent includes any one of benzene, toluene, xylene, cyclohexane, and petroleum ether, or a mixture of at least two of them.

[0022] Furthermore, in S1, the specific operation of gradient heating to 180°C and reacting for 5 hours is: gradient heating is divided into 5 gradients, each gradient heating is 16°C, and each gradient reaction is 1 hour.

[0023] Furthermore, in S2, the polyamide includes PA6 and / or PA610.

[0024] In a second aspect, the present invention provides a rubber resin, which is prepared by the above-mentioned preparation method.

[0025] In a third aspect, the present invention provides an application of a rubber resin, wherein the rubber resin is prepared by the above-mentioned preparation method, and the rubber resin is mixed with C5 petroleum resin to prepare rubber products, and the mass ratio of the rubber resin to the C5 resin is 3:(4-7).

[0026] C5 petroleum resin has good compatibility with the rubber resin. The addition of C5 petroleum resin can reduce the production cost of rubber products without damaging the quality and performance of rubber products, and even help to further improve the initial adhesion, peel strength and heat resistance of rubber products.

[0027] The present invention has the following beneficial effects:

[0028] 1. In the preparation of the rubber resin of the present invention, the introduction of boron element greatly increases the thermal stability of the resin; polyamide has good toughness and thermal stability, and its terminal amino group can undergo hydroxymethylation reaction with formaldehyde under acidic conditions, and then be introduced into the resin structure by chemical copolymerization through hydroxymethyl condensation, thereby improving the toughness (impact strength) and thermal stability of the resin; single micellar core-shell SiO2 nanoparticles can form bonds with resin molecular chains, enhance interfacial bonding, and improve the toughness (impact strength) and thermal stability of the resin; and, experimentally verified, polyamide and single micellar core-shell SiO2 nanoparticles work synergistically to synergistically improve the toughness (impact strength) and thermal stability of the obtained rubber resin.

[0029] 2. In the preparation of single micellar core-shell SiO2 nanoparticles, the hydrolysis and condensation reaction rates of tetraethyl orthosilicate in an acidic environment (hydrochloric acid aqueous solution with a concentration of 0.85M) are moderate, which is conducive to the formation of a uniform, structurally coherent, complete and loose SiO2 network structure; while in an acidic environment (hydrochloric acid aqueous solution with a concentration of 0.85M), the appropriate acidic conditions of polyether help to maintain the appropriate charge balance inside and outside the micelles, so the micelles formed are more stable; the single micellar core-shell SiO2 nanoparticles obtained in this way are more conducive to improving the toughness (impact strength) and thermal stability of the resin.

[0030] 3. In the preparation of single micellar core-shell SiO2 nanoparticles, dimethyldiethoxysilane, as one of the silicon source precursors, participates in the formation of the structure of SiO2 nanoparticles. Its unique molecular structure can form a specific three-dimensional network structure during the hydrolysis and condensation process, which is crucial for maintaining the specific morphology, size and performance of the nanoparticles. In addition, dimethyldiethoxysilane can also form a specific functional layer on the surface of the nanoparticles, further improving the compatibility and interfacial bonding between the nanoparticles and the resin matrix, thereby improving the toughness (impact strength) and thermal stability of the resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 , a comparative trend diagram of thermal stability (mass retention rate at 600° C.) of the rubber resins obtained in Examples 1-5 of the present invention and Comparative Examples 1-7;

[0032] Figure 2 , a comparative trend chart of the toughness (impact strength) of the rubber resins obtained in Examples 1-5 of the present invention and Comparative Examples 1-7. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below with reference to the embodiments.

[0034] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present invention are all commercially available.

[0035] Example 1: A process for preparing a rubber resin, wherein single micellar core-shell SiO2 nanoparticles and polyamide are composite-modified with phenolic resin to obtain a rubber resin;

[0036] The specific process steps are as follows:

[0037] S1. Add 4 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.08 parts of toluene to remove the water produced by the esterification reaction, heat to 100°C, and then heat in 5 steps, each step heating 16°C, each step reacting for 1 hour, and reacting for 5 hours to obtain a reaction solution.

[0038] S2, cool the reaction liquid obtained in S1 to 90°C, add 0.6 parts of polyamide PA6 (nylon-6 chips), 1.5 parts of paraformaldehyde and 0.3 parts of single micelle core-shell SiO2 nanoparticles, stir and heat to 110°C, continue to react for 1 hour until gel occurs, vacuum dry at 120°C for 4 hours until basically no bubbles are generated, and quickly discharge the material to obtain a gel material. Among them, nylon-6 chips (PA-6 general-purpose standard material) were purchased from Ningbo Yushun Plastic Co., Ltd.; paraformaldehyde (96%) was purchased from Shandong Xinhe New Materials Co., Ltd.

[0039] S3, add 0.8 parts of 10% by mass hexamethylenetetramine aqueous solution to the gel material obtained in S2, stir for 10 minutes, let stand for 40 minutes to form a solid resin, and then crush the solid resin into powder to obtain a rubber resin. Among them, hexamethylenetetramine was purchased from Zhengzhou Hongxiang Chemical Co., Ltd.

[0040] The preparation method of single micellar core-shell SiO2 nanoparticles is as follows:

[0041] A1. Dissolve 6 g of polyether in 94 g of 0.85 M hydrochloric acid aqueous solution, stir at 500 r / min for 1 h at room temperature, and the solution becomes clear and transparent, indicating that the polyether has formed micelles and obtained a homogeneous liquid. The polyether is polyether F-68, which was purchased from Hai'an Petrochemical Plant in Jiangsu Province.

[0042] A2, add 10mL of tetraethyl orthosilicate to the homogeneous liquid obtained in A1, stir at 500r / min for 1.2h at room temperature, and the solution becomes transparent from oily turbidity, indicating that the silicon source precursor tetraethyl orthosilicate is hydrolyzed and condensed in the acidic aqueous solution to form a loose three-dimensional network shell structure, and has been successfully deposited on the interface of the hydrophobic segment and the hydrophilic segment of the micelle to obtain a deposition liquid. Among them, tetraethyl orthosilicate SI28 (excellent product) was purchased from Guangzhou Weilina Chemical Co., Ltd.

[0043] A3, add 0.8g of stop solution dimethyldiethoxysilane to the sediment solution obtained in A2, dialyze (molecular weight cutoff 8000-14400) for 48 hours, and replace deionized water every about 1 hour to remove small molecular impurities such as HCL and EtOH produced by hydrolysis in the solution; monitor the dialysis process by measuring the pH value of the dialysate; the initial pH value is lower than 1, and after 48 hours, the pH value reaches about 6, and the dialysis is terminated to obtain the dialysate. Among them, dimethyldiethoxysilane was purchased from Hubei Xinmingtai Chemical Co., Ltd.

[0044] A4. Filter the dialysate obtained in A3 with a 0.22 μm polytetrafluoroethylene filter to remove possible large particles, thereby obtaining the monomicelle core-shell SiO2 nanoparticles.

[0045] Example 2: A process for preparing a rubber resin, wherein single micellar core-shell SiO2 nanoparticles and polyamide are composite-modified with phenolic resin to obtain a rubber resin;

[0046] The specific process steps are as follows:

[0047] S1. Add 3.8 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.05 parts of xylene to remove the water produced by the esterification reaction, heat to 100°C, and then heat in 5 steps, each step heating 16°C, each step reacting for 1 hour, and reacting for 5 hours to obtain a reaction solution.

[0048] S2. Cool the reaction solution obtained in S1 to 90°C, add 0.5 parts of PA6 (nylon-6 chips), 1 part of paraformaldehyde and 0.2 parts of single micellar core-shell SiO2 nanoparticles, stir and heat to 110°C, continue to react for 1 hour until gelation occurs, vacuum dry at 120°C for 4 hours until almost no bubbles are generated, and quickly discharge the material to obtain a gel material.

[0049] S3. Add 0.5 parts of 10% by mass hexamethylenetetramine aqueous solution to the gel material obtained in S2, stir for 10 minutes, and let stand for 40 minutes to form a solid resin. Then crush the solid resin into powder to obtain a rubber resin.

[0050] Example 3: A process for preparing a rubber resin, wherein single micellar core-shell SiO2 nanoparticles and polyamide are composite-modified with phenolic resin to obtain a rubber resin;

[0051] The specific process steps are as follows:

[0052] S1. Add 4.6 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.1 part of xylene to remove the water produced by the esterification reaction, heat to 100°C, and then heat in 5 steps, each step heating 16°C, each step reacting for 1 hour, and reacting for 5 hours to obtain a reaction solution.

[0053] S2. Cool the reaction solution obtained in S1 to 90°C, add 0.8 parts of PA6 (nylon-6 chips), 2 parts of paraformaldehyde and 0.4 parts of single micellar core-shell SiO2 nanoparticles, stir and heat to 110°C, continue to react for 1 hour until gelation occurs, vacuum dry at 120°C for 4 hours until almost no bubbles are generated, and quickly discharge the material to obtain a gel material.

[0054] S3. Add 1 part of 10% by mass hexamethylenetetramine aqueous solution to the gel material obtained in S2, stir for 10 minutes, and let stand for 40 minutes to form a solid resin. Then crush the solid resin into powder to obtain a rubber resin.

[0055] Example 4: A process for preparing a rubber resin, wherein single micellar core-shell SiO2 nanoparticles and polyamide are composite-modified with phenolic resin to obtain a rubber resin;

[0056] The specific process steps are as follows:

[0057] S1. Add 4.2 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.09 parts of xylene to remove the water produced by the esterification reaction, heat the mixture to 100°C, and then heat the mixture in 5 steps, each step heating 16°C, and each step reacting for 1 hour. The reaction mixture reacts for 5 hours to obtain a reaction solution.

[0058] S2. Cool the reaction liquid obtained in S1 to 90°C, add 0.5 parts of PA6 (nylon-6 chips), 1 part of polyformaldehyde and 0.2 parts of single micellar core-shell SiO2 nanoparticles, stir and heat to 110°C, continue to react for 1 hour until gelation occurs, vacuum dry at 120°C for 4 hours until almost no bubbles are generated, and quickly discharge the material to obtain a gel material.

[0059] S3. Add 0.5 parts of 10% by mass hexamethylenetetramine aqueous solution to the gel material obtained in S2, stir for 10 minutes, and let stand for 40 minutes to form a solid resin. Then crush the solid resin into powder to obtain a rubber resin.

[0060] Example 5: A process for preparing a rubber resin, wherein single micellar core-shell SiO2 nanoparticles and polyamide are composite-modified with phenolic resin to obtain a rubber resin;

[0061] The specific process steps are as follows:

[0062] S1. Add 4.6 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.05 parts of xylene to remove the water produced by the esterification reaction, heat to 100°C, and then heat in 5 steps, each step heating 16°C, each step reacting for 1 hour, and reacting for 5 hours to obtain a reaction solution.

[0063] S2. Cool the reaction solution obtained in S1 to 90°C, add 0.5 parts of PA6 (nylon-6 slices), 1 part of paraformaldehyde and 0.2 parts of single micellar core-shell SiO2 nanoparticles, stir and heat to 110°C, continue to react for 1 hour until gelation occurs, vacuum dry at 120°C for 4 hours until almost no bubbles are generated, and quickly discharge the material to obtain a gel material.

[0064] S3. Add 1 part of 10% by mass hexamethylenetetramine aqueous solution to the gel material obtained in S2, stir for 10 minutes, and let stand for 40 minutes to form a solid resin. Then crush the solid resin into powder to obtain a rubber resin.

[0065] Comparative Example 1: The difference between this comparative example and Example 1 is that in the preparation of single micellar core-shell SiO2 nanoparticles, the 0.85M hydrochloric acid aqueous solution is replaced by a 0.85M NaOH aqueous solution.

[0066] Specifically, the preparation method of single micellar core-shell SiO2 nanoparticles is as follows:

[0067] A1. Dissolve 6 g of polyether in 94 g of 0.85 M NaOH aqueous solution, stir at 500 r / min for 1 h at room temperature to obtain a homogeneous liquid.

[0068] A2. Add 10 mL of ethyl orthosilicate to the homogeneous liquid obtained in A1, and stir at 500 r / min for 1.2 h at room temperature to obtain a sedimentation liquid.

[0069] A3. Add 0.8 g of dimethyldiethoxysilane to the sedimentation solution obtained in A2, dialyze (molecular weight cutoff 8000-14400) for 48 hours, and replace the deionized water every about 1 hour to obtain a dialysate.

[0070] A4. Filter the dialysate obtained in A3 with a 0.22 μm polytetrafluoroethylene filter to remove possible large particles, thereby obtaining the monomicelle core-shell SiO2 nanoparticles.

[0071] Comparative Example 2: The difference between this comparative example and Example 1 is that in the preparation of single micellar core-shell SiO2 nanoparticles, the stop solution dimethyldiethoxysilane is deleted.

[0072] Specifically, the preparation method of single micellar core-shell SiO2 nanoparticles is as follows:

[0073] A1. Dissolve 6 g of polyether in 94 g of 0.85 M hydrochloric acid aqueous solution, stir at 500 r / min for 1 h at room temperature to obtain a homogeneous liquid.

[0074] A2. Add 10 mL of ethyl orthosilicate to the homogeneous liquid obtained in A1, and stir at 500 r / min for 1.2 h at room temperature to obtain a sedimentation liquid.

[0075] A3. The sedimentation liquid obtained in A2 was dialyzed (molecular weight cutoff 8000-14400) for 48 hours, and the deionized water was replaced every about 1 hour to obtain a dialysate.

[0076] A4. Filter the dialysate obtained in A3 with a 0.22 μm polytetrafluoroethylene filter to remove possible large particles, thereby obtaining the monomicelle core-shell SiO2 nanoparticles.

[0077] Comparative Example 3: The difference between this comparative example and Example 1 is that in the preparation of single micellar core-shell SiO2 nanoparticles, the 0.85M hydrochloric acid aqueous solution is replaced by a 0.85M NaOH aqueous solution; and the stop solution dimethyldiethoxysilane is deleted.

[0078] Specifically, the preparation method of single micellar core-shell SiO2 nanoparticles is as follows:

[0079] A1. Dissolve 6 g of polyether in 94 g of 0.85 M NaOH aqueous solution, stir at 500 r / min for 1 h at room temperature to obtain a homogeneous liquid.

[0080] A2. Add 10 mL of ethyl orthosilicate to the homogeneous liquid obtained in A1, and stir at 500 r / min for 1.2 h at room temperature to obtain a sedimentation liquid.

[0081] A3. The sedimentation liquid obtained in A2 was dialyzed (molecular weight cutoff 8000-14400) for 48 hours, and the deionized water was replaced every about 1 hour to obtain a dialysate.

[0082] A4. Filter the dialysate obtained in A3 with a 0.22 μm polytetrafluoroethylene filter to remove possible large particles, thereby obtaining the monomicelle core-shell SiO2 nanoparticles.

[0083] Comparative Example 4: The difference between this comparative example and Example 1 is that the single micelle core-shell SiO2 nanoparticles are replaced by commercially available nano-SiO2.

[0084] Comparative Example 5: The difference between this comparative example and Example 1 is that polyamide is deleted in the preparation of the rubber resin.

[0085] Specifically, the preparation process steps of rubber resin are as follows:

[0086] S1. Add 4 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.08 parts of toluene to remove the water produced by the esterification reaction, heat to 100°C, and then heat in 5 steps, each step heating 16°C, each step reacting for 1 hour, and reacting for 5 hours to obtain a reaction solution.

[0087] S2. Cool the reaction solution obtained in S1 to 90°C, add 1.5 parts of paraformaldehyde and 0.3 parts of single micellar core-shell SiO2 nanoparticles, stir and heat to 110°C, continue to react for 1 hour until gelation occurs, vacuum dry at 120°C for 4 hours until almost no bubbles are generated, and quickly discharge the material to obtain a gel material.

[0088] S3. Add 0.8 parts of a 10% by mass aqueous solution of hexamethylenetetramine to the gel material obtained in S2, stir for 10 minutes, and let stand for 40 minutes to form a solid resin. Then crush the solid resin into powder to obtain a rubber resin.

[0089] Comparative Example 6: The only difference between this comparative example and Example 1 is that in the preparation of the rubber resin, the single micelle core-shell SiO2 nanoparticles are deleted.

[0090] Specifically, the preparation process steps of rubber resin are as follows:

[0091] S1. Add 4 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.08 parts of toluene to remove the water produced by the esterification reaction, heat to 100°C, and then heat in 5 steps, each step heating 16°C, each step reacting for 1 hour, and reacting for 5 hours to obtain a reaction solution.

[0092] S2. Cool the reaction solution obtained in S1 to 90°C, add 0.6 parts of PA6 (nylon-6 chips) and 1.5 parts of paraformaldehyde, stir and heat to 110°C, continue to react for 1 hour until gel occurs, vacuum dry at 120°C for 4 hours until almost no bubbles are generated, and quickly discharge the material to obtain a gel material.

[0093] S3. Add 0.8 parts of a 10% by mass aqueous solution of hexamethylenetetramine to the gel material obtained in S2, stir for 10 minutes, and let stand for 40 minutes to form a solid resin. Then crush the solid resin into powder to obtain a rubber resin.

[0094] Comparative Example 7: The only difference between this comparative example and Example 1 is that in the preparation of the rubber resin, polyamide and monomicelle core-shell SiO2 nanoparticles are deleted.

[0095] Specifically, the preparation process steps of rubber resin are as follows:

[0096] S1. Add 4 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to 4-6 with a 35% sulfuric acid aqueous solution, add 0.08 parts of toluene to remove the water produced by the esterification reaction, heat to 100°C, and then heat in 5 steps, each step heating 16°C, each step reacting for 1 hour, and reacting for 5 hours to obtain a reaction solution.

[0097] S2. The reaction solution obtained in S1 was cooled to 90°C, 1.5 parts of paraformaldehyde was added, the temperature was raised to 110°C with stirring, and the reaction was continued for 1 hour until gelation occurred. The reaction was vacuum dried at 120°C for 4 hours until almost no bubbles were generated, and the material was quickly discharged to obtain a gel material.

[0098] S3. Add 0.8 parts of a 10% by mass aqueous solution of hexamethylenetetramine to the gel material obtained in S2, stir for 10 minutes, and let stand for 40 minutes to form a solid resin. Then crush the solid resin into powder to obtain a rubber resin.

[0099] Test example 1: Test item: thermal stability.

[0100] Test subjects: Resins were prepared according to Examples 1-5 and Comparative Examples 1-7.

[0101] Test content: Under the conditions of a temperature test range of 50-600°C and a heating rate of 10°C / min, measure the thermal weight loss of each test object and calculate the mass retention rate (%) at 600°C.

[0102] Test results: See Table 1.

[0103] Test example 2: Test item: impact strength.

[0104] Test subjects: Resins were prepared according to Examples 1-5 and Comparative Examples 1-7.

[0105] Test content: Test the impact strength (KJ / m) of each test object (notched specimen) according to GB / T 1697-2001 2 ).

[0106] Test results: See Table 1.

[0107] Table 1. Test data of test example 1 and test example 2

[0108] Mass retention at 600°C / % <![CDATA[Impact strength / KJ / m 2 > Example 1 71.5 3.17 Example 2 69.8 3.10 Example 3 70.3 3.03 Example 4 70.7 3.08 Example 5 69.3 3.12 Comparative Example 1 65.7 2.79 Comparative Example 2 67.6 2.89 Comparative Example 3 62.7 2.67 Comparative Example 4 59.4 2.47 Comparative Example 5 60.1 2.43 Comparative Example 6 58.5 2.18 Comparative Example 7 51.9 1.95

[0109] Result analysis: Analyze examples 1-5 and combine the data in Table 1 and Figure 1-2It can be seen that the quality retention rate of the rubber resin prepared by the present invention at 600°C is as high as 69.3% or more, and the thermal stability is excellent; at the same time, the impact strength is as high as 3.03KJ / m 2 The above has excellent toughness.

[0110] Analyze Example 1 and Comparative Examples 1-4 and combine the data in Table 1 and Figure 1-2 It can be seen that the single micellar core-shell SiO2 nanoparticles prepared in an acidic environment (hydrochloric acid aqueous solution with a concentration of 0.85M) are more conducive to improving the toughness (impact strength) and thermal stability of the resin; the use of dimethyldiethoxysilane can achieve the effect of improving the toughness (impact strength) and thermal stability of the prepared resin; and the two work synergistically.

[0111] Analyze Example 1 and Comparative Examples 5-7 and combine the data in Table 1 and Figure 1-2 It can be seen that the use of polyamide can improve the toughness (impact strength) and thermal stability of the resin obtained; the use of single micelle core-shell SiO2 nanoparticles can also improve the toughness (impact strength) and thermal stability of the resin obtained; and the two work synergistically to synergistically improve the toughness (impact strength) and thermal stability of the rubber resin.

[0112] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0113] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A process for preparing a rubber resin, characterized in that: The single micellar core-shell SiO2 nanoparticles and polyamide are composite-modified with phenolic resin to obtain the rubber resin; the specific process steps are as follows: S1. Add 3.8-4.6 parts of phenol and 1 part of boric acid into a three-necked flask by weight, adjust the pH to acidic, add 0.05-0.1 parts of water-carrying agent, heat to 100°C, and then gradually heat to 180°C for a total reaction of 5 hours to obtain a reaction solution; S2, cool the reaction solution obtained in S1 to 90°C, add 0.5-0.8 parts of polyamide, 1-2 parts of paraformaldehyde and 0.2-0.4 parts of single micellar core-shell SiO2 nanoparticles, stir and heat to 105-115°C, continue to react for 0.5-2h, vacuum dry at 115-120°C for 2-8h, and quickly discharge to obtain a gel material; S3, adding 0.5-1 parts of a 10% by mass aqueous solution of hexamethylenetetramine to the gel material obtained in S2, stirring for 5-30 minutes, and then standing for 30-50 minutes, and then crushing into powder to obtain the rubber resin; The preparation method of the single micellar core-shell SiO2 nanoparticles is as follows: A1. Dissolve 6 g of polyether F-68 in 94 g of 0.85 M hydrochloric acid aqueous solution, stir at 500 r / min for 1 h at room temperature, the solution becomes clear and transparent, the polyether has formed micelles, and a homogeneous liquid is obtained; A2, add 10mL of tetraethyl orthosilicate to the homogeneous liquid obtained in A1, stir at 500r / min for 1.2h at room temperature, the solution becomes transparent from oily turbidity, the silicon source precursor tetraethyl orthosilicate is hydrolyzed and condensed in the acidic aqueous solution to form a loose three-dimensional network shell structure, and has been successfully deposited on the interface between the hydrophobic segment and the hydrophilic segment of the micelle, to obtain a deposition liquid; A3, after adding 0.8g of the stop solution dimethyldiethoxysilane to the sedimentation liquid obtained in A2, the molecular weight cutoff is 8000-14400 and dialyzed for 48 hours, and the deionized water is replaced every 1 hour; the dialysis process is monitored by measuring the pH value of the dialysate; the initial pH value is lower than 1, and after 48 hours, the pH value reaches 6, the dialysis is terminated, and the dialysate is obtained; A4. Filter the dialysate obtained in A3 through a 0.22 μm polytetrafluoroethylene filter to obtain the monomicelle core-shell SiO2 nanoparticles.

2. The process for preparing the rubber resin according to claim 1, characterized in that: In A1, the stirring condition is: stirring at 500 r / min for 0.8-1.2 h.

3. The process for preparing the rubber resin according to claim 1, characterized in that: In A2, the stirring condition is: stirring at 500 r / min for 1-2 h.

4. The process for preparing the rubber resin according to claim 1, characterized in that: In S1, the specific operation of adjusting the pH to acidic is: using a 35% by mass sulfuric acid aqueous solution to adjust the pH to 4-6.

5. The process for preparing the rubber resin according to claim 1, characterized in that: The water-carrying agent includes any one of benzene, toluene, xylene, cyclohexane and petroleum ether or a mixture of at least two of them.

6. The process for preparing the rubber resin according to claim 1, characterized in that: In S1, the specific operation of gradient heating to 180°C and reacting for 5 h is as follows: gradient heating is performed in 5 gradients, each gradient heating is 16°C, and each gradient reaction is 1 h.

7. The process for preparing the rubber resin according to claim 1, characterized in that: In S2, the polyamide includes PA6 and / or PA610.

8. A rubber resin, characterized in that: The method is prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Thermosetting phenolic resin and preparation method thereof

    CN117264150A

  • Composite phase-change energy storage material for microcapsule and preparation method thereof

    CN101824307A

  • Preparation method of phenol formaldehyde resin integrating heat resistance and toughness

    CN109251289A